The prevalence of anemia in adolescents - A study from Turkey - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
A cross-sectional method was used to study a group of 400 high school students in Kocaeli, Turkey, aged 14 to 16 years, identified among 17,812 high school students. Students from 10 high schools were selected using a random sampling method. Whole blood counts were performed as a screening test for anemia. Serum ferritin levels and, when necessary, hemoglobin electrophoresis were determined for anemic students. Iron medication was prescribed for iron deficiency and genetic counseling was given to adolescents with thalassemia trait. Out of 338 participating students (mean age, 14.72 +/- 0.71 y), anemia (hemoglobin < 12 g/dL for girls and < 13 g/dL for boys) was detected in 17/174 girls (9.7%) and 6/164 boys (3.6%). Iron deficiency anemia was detected in 20/23 (86.9%) of anemic children [15/17 (88.2%) girls and 4/6 (66.6%) boys]. Of 23 students with anemia 2 had beta-thalassemia trait and 2 had both iron deficiency, and beta-thalassemia trait. Etiology of anemia could not be defined in 1 student. The prevalence of adolescent anemia in Kocaeli is almost equal to that in developed countries.
Keywords: anemia; iron deficiency; adolescents; IRON-DEFICIENCY ANEMIA; UNITED-STATES; GIRLS; ACHIEVEMENT; CHILDREN; FREQUENCY